Perception of Farmers of Communal and Individual Stalls Towards the Role of Extension on Integrated Farming in Pelalawan District - Susy Edwina; Evy Maharani; Yeni Kusumawaty; Jumatri Yusri; Yusmini Yusmini (Jurnal Penyuluhan, 2019)
Provision of government assistance to the SISKA (integration of cattle and oilpalm) program has encouraged farmers to form groups. One component of the aid was the communal stall which is a joint enclosure developed in one location. The development of communal stalls is not always successfully maintained by the groups. This study aimed to analyze the perception of SISKA farmers on the role of extension as well as the driving and inhibiting factors of the extension role. The study was conducted in Kecamatan Pangkalan Lesung and Kerumutan Subdistrict of Pelalawan District based on the existence of 11 groups of farmers who still apply SISKA. The analytical method used was perception analysis by average scoring method and perceptual mapping by spiderweb graph. Sampling was conducted by census in 11 farmer groups with a total of 125 members (38 farmers who applied individual stalls and 87 farmers who applied communal stalls). The results showed that the perception towards extension of farmers applying communal stalls was in “good”category, while the perception of farmers applying individual stalls was in “less good” category. The role of extension workers in both systems that has not been functioning was in facilitating farmers to partner.